Atom probe tomography of Ni-base superalloys Allvac 718Plus and Alloy 718 - Viskari, L.; Stiller, K. (Ultramicroscopy, 2011)
Atom probe tomography (APT) allows near atomic scale compositional- and morphological studies of, e.g. matrix, precipitates and interfaces in a wide range of materials. In this work two Ni-base superalloys with similar compositions, Alloy 718 and its derivative Allvac 718Plus, are subject for investigation with special emphasis on the latter alloy. The structural and chemical nuances of these alloys are important for their properties. Of special interest are grain boundaries as their structure and chemistry are important for the materials' ability to resist rapid environmentally induced crack propagation. APT has proved to be suitable for analyses of these types of alloys using voltage pulsed APT. However, for investigations of specimens containing grain boundaries and other interfaces the risk for early specimen fracture is high. Analyses using laser pulsing impose lower electrical field on the specimen thereby significantly increasing the success rate of investigations. Here, the effect of laser pulsing was studied and the derived appropriate acquisition parameters were then applied for microstructural studies, from which initial results are shown. Furthermore, the influence of the higher evaporation field experienced by the hardening γ′ Ni 3(Al,Nb) precipitates on the obtained results is discussed. ► Laser pulsed APT is shown to be a good method for analysis of Ni-based superalloys. ► The evaporation field is shown to be different for different phases which affects reconstructions. ► B and P are shown to segregate to grain boundaries. ► Initial results of δ-phase analysed by APT are shown.